Unlocking Higher Order Thinking With React Strategy: An Effective Solution For 21st Century Learning - Ralmugiz, Uke; Fatmawati, Agustin; Aba, Maria Martini; Syarief, Nur Hasanah; Ketty, Febi; Nizar Zulfikar, Ryan (JTMT: Journal Tadris Matematika, 2025)
The study conducted quantitative research using a True Experimental Design approach known as Pretest-Posttest Control Group Design, involving all grade X students of Senior High School. Cluster Random Sampling was used to select the experimental and control classes. Normality and variant homogeneity tests were conducted. Data analysis utilized a 5% significance level and paired sample t-test for hypothesis testing. Results indicated the REACT strategy effectively improved students' higher-order thinking skills. In the control class, a significant difference was found between pre-test and post-test scores, as well as in the experimental class. Observation sheet assessments showed an average score of 87.5, confirming successful application of the REACT strategy in the learning process. Therefore, the analysis demonstrates the superiority of the REACT strategy over conventional methods in enhancing the higher-order thinking skills of grade X students at Senior High School.